The Learning Anxiety of the students in the Context of Basic Education - Jo-Ann Alindao; Eric B. Catacio; Maria Fresanie T. Alay- Alay; Ligaya C. Belleza; Jeneth R. Omeres; Mycel B. Cezar; Augustus Larida; Remcil B. Neri; Reycher Mortejo; Roberto Suson (Researchparks Publishing, 2022)
This study assessed the Anxiety of the learners in times of new normal in education. The researchers used the descriptive research method to gather information about the respondents’ demographic profile, level of learners anxiety. The data obtained were analyzed using percentage weighted mean, andchi-square to determine the significant degree of relationship between learners profile and the level of learners anxiety. Finding shows that learners have different aniety on different subjects. Moreover, data shows that test anxiety was the most dominant cause of learners anxiety. In addtion, data showed that test and class anxiety are highly correlated with the grade level. This shows that anxiety occurs in different grade level. To sum-up, findings have shown that there is a need to strenghten the connection between students and teachers in order to provide quality education and prevent the existence of academic anxiety.